AUTOPSYCHOLOGICAL COMPETENCE AS A FACTOR OF OCCUPATIONALLY MOBILE SELF-TRANSFORMATION OF A SPECIALIST'S PERSONALITY (Psychology Travelogs, 2023)
The article is devoted to the current problem of researching the autopsychological competence of a specialist from the point of view of its meaningful structuring in order to determine the effective mechanisms of self-knowledge by a person of the complex of "I-professional images" and further occupationally mobile self-transformation of a specialist's personality in the conditions of the dynamics of professional development crises.Autopsychological competence (autocompetency) is defined as an integrative indicator of an individual's ability to develop the subject's intro-individual activity, self-organization, self-knowledge, self-control, and self-correction. The effectiveness of the internal harmonization of intrasubjective communication, the ability to ensure constructive internal orientation and activity of such an introdialogue is determined by the autopsychological competence of the individual.Introharmonization of the multivariate model of "I-image" ("I-professional image") takes place as a certain cognitive scheme, with the participation of which in the process of activity there is a mobile exchange of information between the individual and the environment. Based on the reflexive mechanism of adequate self-assessment of the existing situation and the prospects for its development, this leads to a multivariate modification of the individual's self-knowledge and self-competent self-transformation - bringing it into constructive compliance with the tasks of activity (professional activity).Self-competence implementation of the complex of characteristics of occupational mobility of a specialist is conditioned by his self-psychological ability to adequately identify ways to increase self-efficacy in order to overcome professional crises. This ensures the ability of the specialist's personality to be occupationally mobile - introverted and multivariate, to adjust the strategy or method of action in accordance with the dynamics of changes in the field of professional activity.
Keywords: autopsychological competence; occupational mobility; self-transformation; self-development; introharmonization; multivariability